2017
DOI: 10.1080/14786419.2017.1292268
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and in vitro biological activities of Eremurus spectabilis leaves

Abstract: In the present study, phytochemical investigation of the young leaves of Eremurus spectabilis let to the isolation six compounds (1-6). Their structure was determined by spectroscopic analysis and comparison with the literature data. All compounds were isolated for the first time from E. spectabilis. Isolated compounds and prepared extracts did not show cytotoxic activity against HeLa (Human cervix adenocarcinoma), A-549 (Human alveolar adenocarcinoma), MCF-7 (Human breast adenocarcinoma), mPANC96 (Human pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Isoorientin was isolated from EtOAc extract via Sephadex LH-20 column eluting with MeOH and then silica gel column eluting with CH 2 Cl 2 : MeOH: H 2 O (90:10:1→50:50:5). The structure of isoorientin was elucidated by 1 H NMR, 13 C NMR, 2D NMR and Q-TOF by Sezen Karaoğlan et al 14 .…”
Section: Previous Extraction and Isolation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoorientin was isolated from EtOAc extract via Sephadex LH-20 column eluting with MeOH and then silica gel column eluting with CH 2 Cl 2 : MeOH: H 2 O (90:10:1→50:50:5). The structure of isoorientin was elucidated by 1 H NMR, 13 C NMR, 2D NMR and Q-TOF by Sezen Karaoğlan et al 14 .…”
Section: Previous Extraction and Isolation Studiesmentioning
confidence: 99%
“…Carvone, carvacrol, pentane, (E)-caryophyllene, valencene were found to be as main constituents of the essential oil of E. spectabilis 12 . It is reported that inosine, methyl linolenate, chrysophanol, isoorientin, β-sitosterol and sucrose were also isolated from E. spectabilis 13 . In a previous study, we isolated a high amount of isoorientin from E. spectabilis 14 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The phytochemical composition of Eremurus species have been rarely investigated. In general, isoorientin and methylnaphthalene derivatives have been identified as the predominant phytoconstituents of the plants in this genus [141][142][143][144]. All the isolated compounds are new in E. persicus.…”
Section: Isolation Of Major Constituents From Eremurus Persicusmentioning
confidence: 93%
“…extracts has been rarely carried out. The following compounds have been previously isolated from Eremurus species: aloesaponol III 8-methyl ether, chrysophanol 8-methyl ether, 2-acetyl-1-hydroxy-8-methoxy-3-methylnaphthalene [141][142][143], methyl linolenate, β-sitosterol, isoorientin, inosine [144], chrysophanol [141][142][143][144], altaicusin A, emodin [142], a bi-anthraquinone glycoside, 2-acetyl-1,8-dimethoxy-3-methylnaphthalene, a pre-anthraquinone, 10-(chrysophanol-7'-yl)-10-hydroxychrysophanol-9-anthrone [141], aloesaponol III, and (R)-aloechrysone [143]. By using Folin-Ciocalteu's method, total phenolic contents of various extract of E. spectabilis [10,145,146] were also assessed.…”
Section: Phytochemistry Of the Eremurus Genus And E Persicusmentioning
confidence: 99%
See 1 more Smart Citation